Pyroptosis and HMGB1 Signaling in T2DM-Related Sarcopenia: Current Evidence, Mechanistic Framework, and Exercise Implications - Pengyu Fu; Yuxuan Shi; Songbo Li; Lijing Gong (Health and Metabolism, 2026)
The pathological mechanisms of type 2 diabetes mellitus (T2DM)-related sarcopenia are complex. Classical explanations based on insulin resistance, mitochondrial dysfunction and impaired protein turnover do not fully explain the chronic inflammatory microenvironment observed in diabetic skeletal muscle. Inflammatory cell death and damage-associated molecular pattern responses have attracted increasing attention in metabolic disease research. Evidence from diabetic muscle models, insulin resistance models and other diabetic complications suggests that pyroptosis-related signaling and high mobility group box 1 (HMGB1)-associated inflammatory responses may participate in the metabolic-inflammatory environment associated with T2DM-related sarcopenia. Direct evidence from human skeletal muscle remains limited, and the relationship between these processes has not been clearly defined in this condition. This narrative review summarizes current evidence for inflammasome- and gasdermin-related pyroptotic signaling, HMGB1-associated damage signaling and their potential relevance to diabetic skeletal muscle. It also discusses exercise as a modulator of upstream metabolic and inflammatory stress, including mitochondrial dysfunction, oxidative stress, autophagic flux and selected inflammasome-related markers. Finally, given the current lack of direct skeletal muscle evidence, future research directions are proposed to inform future mechanistic studies and the rational design of exercise interventions for T2DM-related sarcopenia.